2009
DOI: 10.1139/z09-002
|View full text |Cite
|
Sign up to set email alerts
|

Population variation in hypoxic responses of the cichlid Pseudocrenilabrus multicolor victoriae

Abstract: F 1 offspring of the African cichlid Pseudocrenilabrus multicolor victoriae Seegers, 1990 from swamp (low oxygen) and lake (high oxygen) origin were raised under normoxia and submitted to hypoxia acclimation (0.8 ± 0.4 mgÁL -1 ) and normoxia acclimation (7.4 ± 0.3 mgÁL -1 ) for 4 weeks. Haematocrit and lactate dehydrogenase (LDH) specific activities in the liver, white skeletal muscle, heart, and brain were measured. For haematocrit and LDH activities of liver, muscle, and heart, the response to acclimation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Adaptive potential of fish populations to variations in water temperature has been widely investigated to predict the consequences of climate change on fish populations' viability (Beacham & Murray, 1985, 1986Hendry et al, 1998;Haugen & Vollestad, 2000;Jensen et al, 2008). However, few studies investigated the evolutionary potential of populations to lower levels of DO (Crispo & Chapman, 2008, 2011Martinez et al, 2009). These studies were all carried out on African cichlids while hypoxia is also an important stress for fish from the northern hemisphere (Shields & Knight, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive potential of fish populations to variations in water temperature has been widely investigated to predict the consequences of climate change on fish populations' viability (Beacham & Murray, 1985, 1986Hendry et al, 1998;Haugen & Vollestad, 2000;Jensen et al, 2008). However, few studies investigated the evolutionary potential of populations to lower levels of DO (Crispo & Chapman, 2008, 2011Martinez et al, 2009). These studies were all carried out on African cichlids while hypoxia is also an important stress for fish from the northern hemisphere (Shields & Knight, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These adaptations can be physiological (e.g. anaerobic respiration, higher haematocrit; Cooper et al 2002;Martínez et al 2004Martínez et al , 2009, behavioral (e.g. increased use of aquatic surface respiration; Chapman and Liem 1995;Timmerman and Chapman 2004), or morphological (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of oxygen in marine habitats may compress habitable areas for marine organisms (Gallo & Levin, ). This can lead to divergent selection of tolerant genotypes that have better fitness to the prevailing extremes in the habitat (Sultan & Spencer, ; Tobler et al, ), and in favor of physiological tolerance to hypoxia (Chapman, Galis, & Shinn, ; Martinez, Chapman, & Rees, ), and local adaptation. The remarkable hypoxia and anoxia tolerance of S. bibarbatus (Salvanes et al, ; Utne‐Palm et al, ), and also ability to tolerate sulphide shocks (Currie et al, ; Salvanes et al, ), indicate that low bottom oxygen concentration does not limit the distribution and reproduction of S. bibarbatus (Salvanes et al, ; Seivåg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable hypoxia and anoxia tolerance of S. bibarbatus (Salvanes et al, 2015;Utne-Palm et al, 2010), and also ability to tolerate sulphide shocks (Currie et al, 2018;Salvanes et al, 2011), indicate that low bottom oxygen concentration does not limit the distribution and reproduction of S. bibarbatus Seivåg et al, 2016). Some genetic studies of other fish species have shown that long term adaptive response to hypoxia is reflected in gene expression (van der Meer et al, 2005), which in turn can be expressed as physiological and biochemical adaptation (Chapman et al, 2000;Martinez et al, 2009). The present findings are unable to confirm the genetic basis for adaptation to hypoxia in S. bibarbatus, but the study system provides a unique opportunity to investigate the matter using targeted genetic approaches.…”
Section: Loss Of Oxygen In Marine Habitats May Compress Habitable Areasmentioning
confidence: 99%